1974
DOI: 10.1002/dev.420070111
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in tonic immobility in young chicks (Gallus gallus)

Abstract: Tonic immobility (TI) was induced by means of ventral restraint in White Leghorn chicks within 12-hr posthatch (Day 0) and, in independent groups, on succeeding days through Day 10. Durations of immobility and eye closure increased and incidence of immobility termination and vocalization decreased significantly with age. Marked qualitative changes in immobility reactions were also apparent over the finst few posthatch days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1975
1975
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…The continuing increase in incidence in bairdi is much like the pattern observed in chickens (Ratner & Thompson, 1960) and bobwhite quail (Borchelt & Ratner, 1973). Later authors found that chickens would exhibit the response very early and had no increase in incidence, but other parameters of the response did show a pattern of developmental change (Rovee & Kleinman, 1974). In birds, Ratner and Thompson (1960) hypothesized that increasing incidence of immobility is correlated with development of physical independence.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The continuing increase in incidence in bairdi is much like the pattern observed in chickens (Ratner & Thompson, 1960) and bobwhite quail (Borchelt & Ratner, 1973). Later authors found that chickens would exhibit the response very early and had no increase in incidence, but other parameters of the response did show a pattern of developmental change (Rovee & Kleinman, 1974). In birds, Ratner and Thompson (1960) hypothesized that increasing incidence of immobility is correlated with development of physical independence.…”
Section: Discussionmentioning
confidence: 79%
“…In the latter studies, response incidence was complete or high from the beginning but other response parameters changed with age. Response duration and eye closure increased while vocalizations decreased (Rovee & Kleinman, 1974). Bobwhite quail under lateral restraint also exhibit an increase in incidence and duration of immobility with age, but the first strong occurrence is between 9 and 15 days of age (Borchelt & Ratner, 1973).…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Because growing chicks exhibit progressively lengthier durations over this period (Rovee & Kleinman, 1974), either no change or a decrease in response durations could be taken as evidence of habituation. The question of selective habituation was addressed by testing chicks either during the day or at night, at times when the difference in the duration of response was greatest and the variability in duration was least (Rovee et al, 1976).…”
Section: Methodsmentioning
confidence: 99%